On a correlation between EPR data for SASeD doped with Cr³⁺ and soft modes - Lipinski, I.E.; Kuriata, J.; Korynevskii, N.A. (Condensed Matter Physics, 2007)
EPR experimental results obtained for SASeD doped with Cr³⁺ are reported with special emphasis on those observations which reveal the effect of soft modes i.e. the temperature dependence of the DZZ spin- Hamiltonian parameter and the temperature dependence of the EPR linewidth. An extension of the twosublattice model, previously developed and tested for SASD, to include lattice vibrations is presented. The obtained spectrum of bound excitations for the system investigated supports the idea that soft modes contribute to the phase transition at TC = 175 K. The anomaly detected at T1 = 150 K has only a quasisoft mode character and the anomaly detected at T2 = 280 K cannot be related to the effect of soft modes.